Organic silicon artificial leather and preparation method thereof

By coating the artificial leather with abrasion-resistant coating with graphene oxide composite components and modified silica particles on it, the wear problem of artificial leather is solved, significantly improving its wear resistance and UV resistance, and extending its service life.

CN119243490APending Publication Date: 2025-01-03KUSN ACHILLES ARTIFICIAL LEATHER CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411446008.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Artificial leather is prone to wear during use of leather goods, resulting in a decrease in durability, and the prior art is difficult to effectively improve its wear resistance.

Method used

Using wear-resistant coatings containing graphene oxide composite components and silica-modified particles, graphene oxide is modified by polystyrene and polyvinylpyrrolidone to increase its dispersion and stability, and through 2,4-dihydroxyl groups Benzophenone and epoxychlorohydrin graft modified silica particles improve the UV resistance and mechanical properties of the coating.

Benefits of technology

It significantly improves the wear resistance and UV resistance of artificial leather, enhances the stability of the coating and the bonding force with leather, and extends the service life of artificial leather.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to organic silicon artificial leather and a preparation method thereof.The organic silicon artificial leather comprises a leather body and a wear-resistant coating, and the wear-resistant coating is formed by coating the surface of the leather body with wear-resistant paint; the wear-resistant coating comprises the following components in parts by mass: 75-85 parts of polyurethane, 32-40 parts of acrylate, 12-16 parts of a graphite oxide composite component, 4-6 parts of a dispersing agent, 2-4 parts of a flatting agent and 1-3 parts of a defoaming agent, the graphene oxide composite component is prepared from graphene oxide, polyvinylpyrrolidone and polystyrene. The wear-resistant artificial leather has the effect of improving the wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of artificial leather, and in particular to an organosilicon artificial leather and a preparation method thereof. Background Art

[0002] Polyurethane synthetic leather belongs to a type of polyurethane elastomer. It has a soft, natural luster, soft touch, and a strong leather feel. It has excellent mechanical properties such as excellent adhesion to the substrate, flex resistance, and aging resistance. It also has the advantages of good cold resistance, breathability, washability, easy processing, and low price. It is the most ideal substitute for natural leather.

[0003] Artificial leather is widely used in leather decoration, but during the use of leather, it will frequently come into contact with other materials and wear each other. After long-term wear, the durability of artificial leather will decrease, so it needs to be improved. Summary of the invention

[0004] In order to improve the wear resistance of artificial leather, the present application provides a silicone artificial leather and a preparation method thereof.

[0005] The present application provides an organosilicon artificial leather and a preparation method thereof using the following technical solutions: In the first aspect, the present application provides an organosilicon artificial leather, which adopts the following technical solution: An organosilicon artificial leather comprises a leather body and a wear-resistant coating, wherein the wear-resistant coating is formed by coating the wear-resistant coating on the surface of the leather body, and the wear-resistant coating comprises the following components by mass: 75-85 parts of polyurethane, 32-40 parts of acrylate, 12-16 parts of graphite oxide composite component, 4-6 parts of dispersant, 2-4 parts of leveling agent, 1-3 parts of defoaming agent; The graphene oxide composite component comprises graphene oxide, polyvinyl pyrrolidone and polystyrene.

[0006] By adopting the above technical scheme, graphene has excellent mechanical properties, a large specific surface area and excellent thermal conductivity, and can effectively reduce friction and wear. After being added to the wear-resistant coating and coated on the surface of the leather body, it can effectively reduce the wear of the leather. Polyvinyl pyrrolidone is used to load polystyrene to the surface of graphene oxide. While retaining the characteristics of graphene oxide, the dispersibility of graphene oxide in the wear-resistant coating system can be improved, thereby improving the stability of the wear-resistant coating system.

[0007] Preferably, the modified graphene oxide is prepared by the following method: The graphene oxide is mixed with water and ultrasonically treated to obtain a graphene oxide dispersion, polyvinyl pyrrolidone is mixed with water to obtain a polyvinyl pyrrolidone solution, the polyvinyl pyrrolidone solution is mixed with the graphene oxide dispersion, and a mixture is obtained by stirring, the pH value of the mixture is adjusted to alkaline, styrene is added under stirring, and then a potassium persulfate solution is added, and the stirring reaction is maintained, and then hydrazine hydrate is added to continue the reaction, and freeze-drying is performed after the reaction, and the graphene oxide composite material is obtained after grinding.

[0008] By adopting the above technical solution, the van der Waals force between graphene layers is destroyed during the process of polystyrene loading on graphene oxide, and oxygen-containing groups are inserted between the layers, thereby increasing the spacing between graphene oxide sheets, thereby improving the dispersibility and stability of graphene oxide, and further improving the overall wear resistance of the system. At the same time, the oxygen-containing groups on the surface of graphene oxide are reduced, and the thermal stability is also significantly improved.

[0009] Preferably, the mass ratio of graphene oxide, polyvinyl pyrrolidone and styrene is (0.35-0.39):1:1.04.

[0010] By adopting the above technical solution, the mass ratio of graphene oxide, polyvinyl pyrrolidone and polyphenylene is preferably within the above range, which can effectively improve the stability of the graphene oxide composite component.

[0011] Preferably, the pH value of the mixture is 9.1-9.5.

[0012] By adopting the above technical solution, preferably the pH value during the reaction is within the above range, which can further improve the stability of the graphene oxide composite component.

[0013] Preferably, the wear-resistant coating further comprises silica-modified particles, and the silica-modified particles comprise nano-silica, 2,4-dihydroxybenzophenone and epichlorohydrin.

[0014] By adopting the above technical solution, 2,4-dihydroxybenzophenone is a small molecule benzophenone compound. By grafting it on the surface of nano-silica particles, the stability of 2,4-dihydroxybenzophenone can be improved, and it can synergistically enhance the anti-ultraviolet performance of the system with the nano-silica particles, thereby further improving the anti-ultraviolet performance of the wear-resistant coating.

[0015] Preferably, the silicon dioxide modified particles are prepared by the following method: The method comprises the following steps: adding 2,4-dihydroxybenzophenone to obtain a 2,4-dihydroxybenzophenone solution, mixing the 2,4-dihydroxybenzophenone solution with epichlorohydrin, then adding a sodium hydroxide solution to react, removing the organic solvent by rotary evaporation after extraction, purifying and drying to obtain a composite; dispersing nano-silicon dioxide in toluene, adding a coupling agent, reacting, extracting by centrifugation, and redispersing in toluene, adding the composite to react while maintaining stirring, and washing and drying after centrifugation to obtain silicon dioxide modified particles.

[0016] By adopting the above technical scheme, 2,4-dihydroxybenzophenone is connected to the epoxy active group and then grafted to the surface of silica to obtain modified silica particles, so that the benzophenone compounds and silica particles can synergistically improve the anti-ultraviolet performance of the wear-resistant coating, and a more stable system can be obtained. At the same time, the compatibility of silica particles is improved, so that the bonding force between the wear-resistant coating and the leather surface is improved, and the stability of the wear-resistant coating is further improved.

[0017] Preferably, the mass ratio of the 2,4-dihydroxybenzophenone to acetone, epichlorohydrin to silica particles is 0.4:1:(2.7-2.9).

[0018] By adopting the above technical solution, the mass ratios of 2,4-dihydroxybenzophenone to acetone, and epichlorohydrin to silica particles are preferably within the above ranges, which can further improve the stability of the silica modified particles.

[0019] Preferably, the coupling agent comprises 3-aminopropyltriethoxysilane.

[0020] Preferably, the mass ratio between the graphene oxide composite component and the silicon dioxide modified particles is (2-3):1.

[0021] By adopting the above technical solution, the mass ratio between the graphene oxide composite component and the silicon dioxide modified particles is preferably within the above range, which can further improve the comprehensive performance of the wear-resistant coating.

[0022] In a second aspect, the present application provides a method for preparing silicone artificial leather, which adopts the following technical solution: A method for preparing organosilicon artificial leather comprises the following steps: The wear-resistant coating is coated on the surface of the leather body, so that the wear-resistant coating forms a wear-resistant coating on the surface of the leather body to obtain an organosilicon artificial leather product.

[0023] In summary, the present application includes at least one of the following beneficial technical effects: 1. After the wear-resistant coating is applied on the surface of the leather body, a wear-resistant coating is formed on the surface of the leather body. The graphene oxide composite component is added to the wear-resistant coating system, which can effectively improve the wear resistance of the wear-resistant coating as a whole, so as to improve the overall stability of the system. After the graphene oxide is modified by polystyrene and polyvinyl pyrrolidone, the spacing between the graphene oxide sheets is significantly improved, so that the graphene oxide can be more evenly dispersed in the wear-resistant coating system, further improving the stability of the system; 2. Silica modified particles are also added to the wear-resistant coating system. Through the grafting between the coupling agent and 2,4-dihydroxybenzophenone and silica, the silica surface is connected to the benzophenone compound, which synergistically improves the UV resistance of the system with the silica particles, thereby improving the overall UV resistance of the artificial leather. At the same time, the silica modified particles and the graphene oxide composite components can synergistically improve the overall UV resistance and wear resistance of the wear-resistant coating system, and at the same time improve the overall mechanical properties of the wear-resistant coating, making the wear-resistant coating more stable. DETAILED DESCRIPTION

[0024] The present application is further described in detail below with reference to the embodiments: Description of raw materials: All raw materials in the examples can be obtained commercially; among them, the coupling agent is 3-aminopropyltriethoxysilane (CAS No.: 919-30-2); the dispersant is efka-4010 dispersant; the leveling agent is BYK leveling agent; and the defoaming agent is polyethylene glycol ether (CAS No.: 31017-83-1).

[0025] Example 1 Preparation of silica modified particles: 1.46 g of 2,4-dihydroxybenzophenone (CAS No.: 131-56-6) was added to 20 ml of acetone to obtain a 2,4-dihydroxybenzophenone solution. The 2,4-dihydroxybenzophenone solution was mixed with 3.66 g of epichlorohydrin (CAS No.: 106-89-8) and heated to 80°C. Then, 20 mL of a 2.5 wt% sodium hydroxide aqueous solution was added to the system, and the reaction was continued for 2 h. The system was then extracted with ethyl acetate, and then the organic solvent was removed by rotary evaporation. Finally, the system was passed through a silica gel layer. The mixture was purified by column chromatography, transferred to a vacuum drying environment at 50°C for 12 hours to obtain a composite; 9.88 g of nano-silica was dispersed in 500 ml of toluene, 1.2 g of a coupling agent was added under reflux at 100°C, and the reaction was continued for 4 hours. The mixture was centrifuged and extracted with toluene for 3 times, and then redispersed in toluene. While maintaining stirring, the prepared composite was added, and the reaction was continued at 40°C for 12 hours. After centrifugation, the mixture was washed with toluene and dried under a vacuum environment at 60°C for 18 hours to obtain silica-modified particles.

[0026] Preparation of graphene oxide composites: 11.72 g of graphene oxide was mixed with 1000 g of deionized water and ultrasonically treated for 15 min to obtain a graphene oxide dispersion, 33.47 g of polyvinyl pyrrolidone (CAS No.: 9003-39-8) was mixed with 180 g of deionized water to obtain a polyvinyl pyrrolidone solution, the polyvinyl pyrrolidone solution was mixed with the graphene oxide dispersion, magnetically stirred for 30 min to obtain a mixture, ammonia water was added to adjust the pH value of the mixture to 9.1, and then 34.81 g of styrene was added under nitrogen protection at a speed of 500 r / min with stirring, and then 25 ml of a 15 mg / mL potassium persulfate aqueous solution was added, stirring was maintained at 90° C. for 6 h, and then 0.75 g of hydrazine hydrate was added, and the reaction was continued for 1 h. After the reaction, the system was freeze-dried at -20° C. for 12 h, and the graphene oxide composite material was obtained after grinding.

[0027] Preparation of wear-resistant coating: Mix 75g of polyurethane, 32g of acrylic acid and 4g of dispersant, stir at 300r / min for 10min, then add 12g of graphene oxide composite component and 6g of silica modified particles, stir at 500r / min for 8min, finally add 2g of leveling agent and 1g of defoaming agent, stir at 800r / min for 5min to obtain a wear-resistant coating.

[0028] Preparation of silicone artificial leather: The wear-resistant coating is coated on the surface of the leather body, and then placed at room temperature for 12 hours, so that the wear-resistant coating forms a wear-resistant coating on the surface of the leather body to obtain a silicone artificial leather product.

[0029] Example 2 Preparation of silica modified particles: 1.4 g of 2,4-dihydroxybenzophenone was added to 20 ml of acetone to obtain a 2,4-dihydroxybenzophenone solution, the 2,4-dihydroxybenzophenone solution was mixed with 3.49 g of epichlorohydrin and heated to 80°C, then 20 mL of a 2.5 wt% sodium hydroxide aqueous solution was added to the system, reacted for 2 h, extracted with ethyl acetate, and then the organic solvent was removed by rotary evaporation, finally purified by a silica gel chromatography column, transferred to a 50°C environment and vacuum dried for 12 h to obtain a composite; 10.11 g of nano-silicon dioxide was dispersed in 500 ml of toluene, 1.2 g of a coupling agent was added under reflux at 100°C, reacted for 4 h, the mixture was centrifuged and extracted with toluene for 3 times, and then redispersed in toluene, and the above-prepared composite was added under stirring, reacted at 40°C for 12 h, washed with toluene after centrifugation, and dried at 60°C in a vacuum environment for 18 h to obtain silica-modified particles.

[0030] Preparation of graphene oxide composite materials: 12.84 g of graphene oxide was mixed with 1000 g of deionized water and ultrasonically treated for 15 minutes to obtain a graphene oxide dispersion, 32.92 g of polyvinyl pyrrolidone was mixed with 180 g of deionized water to obtain a polyvinyl pyrrolidone solution, the polyvinyl pyrrolidone solution was mixed with the graphene oxide dispersion, magnetically stirred for 30 minutes to obtain a mixture, ammonia water was added to adjust the pH value of the mixture to 9.5, and then 34.24 g of styrene was added under nitrogen protection at a speed of 500 r / min with stirring, and then 25 ml of a 15 mg / mL potassium persulfate aqueous solution was added, stirring was maintained at 90° C. for 6 hours, and then 0.75 g of hydrazine hydrate was added, and the reaction was continued for 1 hour. After the reaction, the system was freeze-dried at -20° C. for 12 hours, and the graphene oxide composite material was obtained after grinding.

[0031] Preparation of wear-resistant coating: Mix 85g of polyurethane, 40g of acrylic acid and 6g of dispersant, stir at 300r / min for 10min, then add 16g of graphene oxide composite component and 5.33g of silica modified particles, stir at 500r / min for 8min, finally add 4g of leveling agent and 3g of defoaming agent, stir at 800r / min for 5min to obtain a wear-resistant coating.

[0032] Preparation of silicone artificial leather: The wear-resistant coating is coated on the surface of the leather body, and then placed at room temperature for 12 hours, so that the wear-resistant coating forms a wear-resistant coating on the surface of the leather body to obtain a silicone artificial leather product.

[0033] Example 3 Preparation of silica modified particles: 1.43 g of 2,4-dihydroxybenzophenone was added to 20 ml of acetone to obtain a 2,4-dihydroxybenzophenone solution, the 2,4-dihydroxybenzophenone solution was mixed with 3.57 g of epichlorohydrin and heated to 80°C, then 20 mL of a 2.5 wt% sodium hydroxide aqueous solution was added to the system, reacted for 2 hours, extracted with ethyl acetate, and then the organic solvent was removed by rotary evaporation, finally purified by a silica gel chromatography column, transferred to a 50°C environment and vacuum dried for 12 hours to obtain a composite; 10 g of nano-silicon dioxide was dispersed in 500 ml of toluene, 1.2 g of a coupling agent was added under reflux at 100°C, reacted for 4 hours, the mixture was centrifuged and extracted with toluene for 3 times, and then redispersed in toluene, and the above-prepared composite was added under stirring, reacted at 40°C for 12 hours, washed with toluene after centrifugation, and dried at 60°C in a vacuum environment for 18 hours to obtain silica-modified particles.

[0034] Preparation of graphene oxide composite materials: 12.82 g of graphene oxide was mixed with 1000 g of deionized water and ultrasonically treated for 15 min to obtain a graphene oxide dispersion, 33.19 g of polyvinyl pyrrolidone was mixed with 180 g of deionized water to obtain a polyvinyl pyrrolidone solution, the polyvinyl pyrrolidone solution was mixed with the graphene oxide dispersion, magnetically stirred for 30 min to obtain a mixture, ammonia water was added to adjust the pH value of the mixture to 9.3, and then 33.99 g of styrene was added under nitrogen protection at a speed of 500 r / min with stirring, and then 25 ml of a 15 mg / mL potassium persulfate aqueous solution was added, stirring was maintained at 90° C. for 6 h, and then 0.75 g of hydrazine hydrate was added, and the reaction was continued for 1 h. After the reaction, the system was freeze-dried at -20° C. for 12 h, and the graphene oxide composite material was obtained after grinding.

[0035] Preparation of wear-resistant coating: Mix 80g of polyurethane, 36g of acrylic acid and 5g of dispersant, stir at 300r / min for 10min, then add 14g of graphene oxide composite component and 5.6g of silica modified particles, stir at 500r / min for 8min, finally add 3g of leveling agent and 2g of defoaming agent, stir at 800r / min for 5min to obtain a wear-resistant coating.

[0036] Preparation of silicone artificial leather: The wear-resistant coating is coated on the surface of the leather body, and then placed at room temperature for 12 hours, so that the wear-resistant coating forms a wear-resistant coating on the surface of the leather body to obtain a silicone artificial leather product.

[0037] Example 4 Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that in Example 4, when preparing silica-modified particles, 1.58 g of 2,4-dihydroxybenzophenone, 3.95 g of epichlorohydrin and 9.47 g of nano-silica are used.

[0038] Example 5 Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that in Example 5, when preparing silicon dioxide particles, 1.3 g of 2,4-dihydroxybenzophenone, 3.26 g of epichlorohydrin and 10.44 g of nano-silica are used.

[0039] Example 6 Example 6 is based on Example 3. In Example 6, when preparing the silica-modified particles, the nano-silica is not treated with a coupling agent.

[0040] Example 7 Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that in Example 7, when preparing the graphene oxide composite component, 10.85 g of graphene oxide, 33.9 g of polyvinyl pyrrolidone, and 35.25 g of styrene are used.

[0041] Example 8 Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that in Example 8, when preparing the graphene oxide composite component, 13.66 g of graphene oxide, 32.52 g of polyvinyl pyrrolidone, and 33.82 g of styrene are used.

[0042] Example 9 Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that in Example 9, when preparing the graphene oxide composite component, the pH value of the mixture is adjusted to 8.5.

[0043] Example 10 Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that in Example 10, when preparing the graphene oxide composite component, the pH value of the mixture is adjusted to 10.

[0044] Embodiment 11 Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that 9.33 g of modified silica particles are added in Example 11.

[0045] Example 12 Example 12 is based on Example 3. The difference between Example 12 and Example 3 is that 4 g of silica modified particles are added in Example 12.

[0046] Comparative Example 1 Comparative Example 1 is based on Example 3, and the modified silica particles in Comparative Example 1 are replaced with ordinary silica nanoparticles.

[0047] Comparative Example 2 Comparative Example 2 is based on Example 3, but no silicon dioxide modified particles are added in Comparative Example 2.

[0048] Comparative Example 3 Comparative Example 3 is based on Example 3, and the graphene oxide composite component is replaced by ordinary graphene oxide in Comparative Example 3.

[0049] Comparative Example 4 Comparative Example 4 is based on Example 3, and the graphene oxide composite component is replaced by an equal amount of polyurethane in Comparative Example 4.

[0050] Performance testing The samples of Examples 1-12 and Comparative Examples 1-4 were sampled and the following performance tests were performed: (1) Wear resistance test The wear resistance of leather was tested according to GB / T 2726-2005. Each sample was tested 3 times and the test results were filled in Table 1.

[0051] (3) Ultraviolet light transmittance Test the UV transmittance of the wear-resistant coating. Test each sample 3 times and fill in the test results in Table 1.

[0052] (2) UV resistance test The samples were subjected to UV aging according to ASTM G154-16. UVA-340 lamps were used to age the samples at 60°C for 8 hours, and then condensed at 50°C for 4 hours. The appearance of the samples was observed. Each sample was tested 3 times, and the test results were filled in Table 1.

[0053] Table 1 Performance test results of samples of Examples 1-12 and Comparative Examples 1-4 Test items Wear test UV transmittance / % Appearance color after UV aging Example 1 No wear and tear, no peeling 99.15 No discoloration Example 2 No wear and tear, no peeling 99.44 No discoloration Example 3 No wear and tear, no peeling 99.85 No discoloration Example 4 Basically no wear and tear, no peeling 96.54 Almost no fading Example 5 Basically no wear and tear, no peeling 96.25 Almost no fading Example 6 Slight wear, no peeling 93.63 Slightly faded Example 7 Basically no wear and tear, no peeling 96.08 Almost no fading Example 8 Basically no wear and tear, no peeling 96.32 Almost no fading Example 9 Basically no wear and tear, no peeling 96.25 Almost no fading Example 10 No wear and tear, no peeling 98.68 No discoloration Embodiment 11 Slight wear, no peeling 92.92 Slightly faded Example 12 Slight wear, no peeling 92.31 Slightly faded Comparative Example 1 Wear, no peeling 89.22 There is fading phenomenon Comparative Example 2 Moderate wear, slight peeling 84.28 Fading is more obvious Comparative Example 3 Wear, no peeling 88.94 There is fading phenomenon Comparative Example 4 Moderate wear, slight peeling 81.08 Fading is more obvious Combined with Table 1, it can be seen that the examples 1-3 are not worn or peeled off after the wear resistance test, indicating that the artificial leather prepared in the present application has good wear resistance; the ultraviolet light transmittance of the coatings of examples 1-3 is 99.15% or above, and the anti-ultraviolet performance is x or above, indicating that the artificial leather prepared in the present application has good anti-ultraviolet performance.

[0054] In Example 4 and Example 5, when preparing silica-modified particles, the mass ratios of 2,4-dihydroxybenzophenone, epichlorohydrin and nano-silica are not within the range specified in the present application. When the content of nano-silica is too little, it is difficult to graft more benzophenone compounds on the surface of the silica particles. At the same time, the reduction of silica reduces the anti-ultraviolet effective components of the system, which affects the anti-ultraviolet performance of the system and the overall wear resistance of the system. When the content of nano-silica is too much, too little benzophenone compounds decrease, making it difficult to synergistically improve the anti-ultraviolet performance with silica particles. At the same time, too much nano-silica agglomerates in the system, thereby affecting the overall stability of the coating system.

[0055] In Example 6, no coupling agent is used to treat the surface of the nano-silica, which makes it difficult for the surface of the nano-silica to carry active groups, and thus it is difficult to stably graft the complex to the surface of the nano-silica. As a result, it is difficult for the anti-ultraviolet agent to exist more stably in the system, affecting the overall ultraviolet resistance of the system.

[0056] In Example 7 and Example 8, when preparing the graphene oxide composite component, the mass ratios of graphene oxide, polyvinyl pyrrolidone and styrene are not within the range specified in the present application. When the content of graphene oxide is too little, it is difficult to combine to generate more polystyrene in the system, which reduces the anti-ultraviolet performance of the system. When the content of graphene oxide is too much, the graphene oxide will agglomerate in the system, thereby affecting the overall stability of the coating system.

[0057] In Example 9 and Example 10, when preparing the graphene oxide composite component, the pH value of the mixture is not within the range specified in the present application. When the pH value of the mixture is too low, the polymerization effect of the system is difficult to proceed further, and the prepared graphene oxide is difficult to be better dispersed in the system, thereby affecting the comprehensive performance of the system; when the pH value of the mixture is too high, the polymerization reaction of the system is too fast, so that the stability of the graphene oxide composite component product is affected, so the performance of Example 9 and Example 10 are both reduced.

[0058] The mass ratios between the silica-modified particles and the graphene oxide composite components in Examples 11 and 12 are not within the scope of the present application. When the content of the silica-modified particles is too much, there are too many inorganic fillers in the system, and the dispersibility of the silica-modified particles and the graphene oxide composite materials is reduced, affecting the overall stability of the system; when the content of the silica-modified particles decreases, the anti-ultraviolet active ingredients and wear resistance in the system are reduced, and it is difficult to synergistically improve the overall wear resistance of the system with the graphene oxide composite components.

[0059] In Comparative Example 1, the nano-silica was not modified, and the dispersibility of the unmodified silica in the system decreased. At the same time, the overall anti-ultraviolet performance of the system was also reduced after the benzophenone component was not grafted.

[0060] In Comparative Example 2, no silicon dioxide modified particles were added, which resulted in a decrease in the overall performance of the system.

[0061] In Comparative Example 3, the graphene oxide composite component is replaced with ordinary graphene oxide. The dispersion performance of the unmodified graphene oxide is difficult to improve, and agglomeration occurs in the system, thereby affecting the overall stability of the system.

[0062] In Comparative Example 4, no graphene oxide composite component is added, which makes it difficult to further improve the overall wear resistance and anti-exterior performance of the system.

[0063] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. An organosilicon artificial leather, characterized in that: The leather body and the wear-resistant coating are formed by coating the wear-resistant coating on the surface of the leather body. The wear-resistant coating includes the following components by mass: 75-85 parts of polyurethane, 32-40 parts of acrylate, 12-16 parts of graphite oxide composite component, 4-6 parts of dispersant, 2-4 parts of leveling agent, 1-3 parts of defoaming agent; The graphene oxide composite component comprises graphene oxide, polyvinyl pyrrolidone and polystyrene.

2. The organosilicon artificial leather according to claim 1, characterized in that: The modified graphene oxide is prepared by the following method: The graphene oxide is mixed with water and ultrasonically treated to obtain a graphene oxide dispersion, polyvinyl pyrrolidone is mixed with water to obtain a polyvinyl pyrrolidone solution, the polyvinyl pyrrolidone solution is mixed with the graphene oxide dispersion, and a mixture is obtained by stirring, the pH value of the mixture is adjusted to alkaline, styrene is added under stirring, and then a potassium persulfate solution is added, and the stirring reaction is maintained, and then hydrazine hydrate is added to continue the reaction, and freeze-drying is performed after the reaction, and the graphene oxide composite material is obtained after grinding.

3. The organosilicon artificial leather according to claim 2, characterized in that: The mass ratio of the graphene oxide, polyvinyl pyrrolidone and styrene is (0.35-0.39):1:1.

04.

4. The organosilicon artificial leather according to claim 3, characterized in that: The pH value of the mixture is 9.1-9.

5.

5. The organosilicon artificial leather according to claim 1, characterized in that: The wear-resistant coating further comprises silicon dioxide modified particles, wherein the silicon dioxide modified particles comprise nano silicon dioxide, 2,4-dihydroxybenzophenone and epichlorohydrin.

6. The organosilicon artificial leather according to claim 5, characterized in that: The silicon dioxide modified particles are prepared by the following method: The method comprises the following steps: adding 2,4-dihydroxybenzophenone to obtain a 2,4-dihydroxybenzophenone solution, mixing the 2,4-dihydroxybenzophenone solution with epichlorohydrin, then adding a sodium hydroxide solution to react, removing the organic solvent by rotary evaporation after extraction, purifying and drying to obtain a composite; dispersing nano-silicon dioxide in toluene, adding a coupling agent, reacting, extracting by centrifugation, and redispersing in toluene, adding the composite to react while maintaining stirring, and washing and drying after centrifugation to obtain silicon dioxide modified particles.

7. The organosilicon artificial leather according to claim 6, characterized in that: The mass ratio of the 2,4-dihydroxybenzophenone to acetone, epichlorohydrin to silicon dioxide particles is 0.4:1:(2.7-2.9).

8. The organosilicon artificial leather according to claim 6, characterized in that: The coupling agent includes 3-aminopropyltriethoxysilane.

9. The organosilicon artificial leather according to claim 5, characterized in that: The mass ratio between the graphene oxide composite component and the silicon dioxide modified particles is (2-3):

1.

10. A method for preparing the organosilicon artificial leather according to claim 1, characterized in that: The steps include: The wear-resistant coating is coated on the surface of the leather body, so that the wear-resistant coating forms a wear-resistant coating on the surface of the leather body to obtain an organosilicon artificial leather product.

Citation Information

Cited By

  • Environment-friendly fluorocarbon coating and preparation method thereof

    CN122188454A